Mycobacterial Phenolic Glycolipids with a Simplified Lipid Aglycone Modulate Cytokine Levels through Toll‐Like Receptor 2. Issue 16 (2nd October 2013) - Elsaidi, Hassan R. H.; Barreda, Daniel R.; Cairo, Christopher W.; Lowary, Todd L.
Abstract Phenolic glycolipids (PGLs) are virulence factors present in the cell walls of many pathogenic mycobacteria. PGLs have been implicated in various aspects of mycobacterial disease, but there are limited structure–activity data available for these molecules. We report here the preparation of seven synthetic PGL analogues, differing from the native compounds in the replacement of the complex phenolic lipid moiety with a p‐methoxyphenyl group. The ability of these compounds to stimulate or inhibit the production of cytokines (TNF‐α, IL‐1β, IL‐6, MCP‐1) and nitric oxide (NO) was then evaluated by ELISA‐based assays. None of the compounds stimulated the production of these biological signalling molecules. In contrast, they each displayed concentration‐dependent inhibitory activity, related to the methylation pattern of the molecule and mediated by Toll‐like receptor 2. Additional studies revealed that native PGL‐I from Mycobacterium leprae and a synthetic PGL‐I analogue containing a simplified lipid domain had enhanced inhibitory activities relative to the corresponding analogues containing the p‐methoxyphenyl aglycone; however, the natural lipid phenolthiocerol was only weakly active. These studies reveal that synthetic molecules of this type can be used as probes for PGL function. Moreover, their ease of synthesis relative to the natural glycolipids, as well as their more favourable aqueous solubility, should allow for more thorough structure–activity relationship studies.